Fairness Evaluation and Comparison of Current Congestion Control Techniques. - Usman Ahmad; Md Asri Bin Ngadi; Ismail Fauzi Bin Isnin (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
Transmission Control Protocol (TCP) is used by many applications on the Internet for the reliable data transmission. TCP does not able to utilize the available link bandwidth quickly and efficiently in High bandwidth short distance (HBSD) and high bandwidth long distance (HBLD) networks. Many congestion control techniques also known as TCP variants are developed to solve these problems in different network environments. In this paper an experimental analysis is done for the performance evaluation of TCP CUBIC, TCP Compound, TCP Reno and High speed TCP in term of Inter and Intra Protocol fairness by using Network Simulator 2 (NS-2). Results show that the performance of TCP CUBIC pathetically down and TCP Compound and TCP Reno shows good performance in term of protocol fairness. However, these congestion control techniques still need more improvement for the utilization of available link bandwidth in HBLD networks and other network resources.